Binge Eating Disorder as Seen in the Whale (2022) Movie - Bagas Kurniawan; Dina Amelia (Universitas Islam Negeri Palopo, 2026)
This study aims to analyze the portrayal of Binge Eating Disorder (BED) in the film The Whale (2022) through a literary psychology approach and cinematic narrative theory. The study focuses on the main character, Charlie, by identifying behaviors that reflect BED symptoms based on DSM-5 diagnostic criteria. This research uses a descriptive qualitative method with narrative analysis techniques and visual observation of key scenes that represent the character's psychological condition. The findings show that the linear narrative structure and the use of emotional devices in the film succeed in building audience empathy and strengthening understanding of the psychological symptoms of BED sufferers. Thus, this film is not only a cinematic work, but also serves as an effective educational medium in raising public awareness of mental health issues, especially eating disorders.